2021
DOI: 10.1021/acs.nanolett.1c02208
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Water Slip Using Atomic-Scale Defects: Friction on Realistic Hexagonal Boron Nitride Surfaces

Abstract: Atomic-scale defects are ubiquitous in nanomaterials, yet their role in modulating fluid flow is inadequately understood. Hexagonal boron nitride (hBN) is an important two-dimensional material with applications in desalination and osmotic power. Although pristine hBN offers higher friction to the flow of water than graphene, we show here that certain defects can enhance water slippage on hBN. Using classical molecular dynamics simulations assisted by quantum-mechanical density functional theory, we compute the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Yet others have used the density-derived electrostatic and chemical (DDEC) method and electrostatic potential fitting (ESP) method (e.g., Jafarzadeh et al) to calculate partial charges. In previous work, we showed that ESP-based charges are not able to predict correctly the electrostatic potential above defects in hBN . In Section S10, we show that DDAP (using default parameters), Hirshfeld, Mulliken, and DDEC partial charges are also not suitable for predicting the electrostatic potential above nanopores in hBN.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Yet others have used the density-derived electrostatic and chemical (DDEC) method and electrostatic potential fitting (ESP) method (e.g., Jafarzadeh et al) to calculate partial charges. In previous work, we showed that ESP-based charges are not able to predict correctly the electrostatic potential above defects in hBN . In Section S10, we show that DDAP (using default parameters), Hirshfeld, Mulliken, and DDEC partial charges are also not suitable for predicting the electrostatic potential above nanopores in hBN.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Overall, these results consolidate the picture of dipolar environment-tuned defects, whose properties are affected by changes in the sensing hemisphere with volume ∼ 2/3π 3 dip , which encloses fewer than 100 molecules in the case of acetonitrile. Beyond passive diffusion and dielectric sensing of confined liquids, tracking defect activation dynamics in confinement may be used to directly image nanoscale flow and study its interplay with defects 54 . While a macroscopic control over the ensemble surface charge of nanofluidic devices with light was found to be useful for biomolecule detection 55 and energy harvesting applications 56,57 , the possibility to address single charges in confinement suggested by our results may reveal fundamentally new phenomena such as correlated ion transport 52 .…”
Section: Integration In Single-digit Nanofluidic Systemsmentioning
confidence: 99%
“…Hexagonal boron nitride (hBN) is an inorganic two-dimensional (2D) material that has found applications in seawater desalination, , osmotic power harvesting, and biological sensors . Understanding the wetting and fluidic properties of 2D materials is essential in such applications because of the resultant intimate contact between liquids and the solid surface. In this regard, the interfacial properties of a solid surface can be impacted by any defects or roughness present in it. For example, the equilibrium contact angle and slip length for fluid flow can depend on the nanoscale structure of the solid. However, there is a lack of understanding of the wetting and frictional behavior of solids containing atomic-scale defects and/or roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The wetting and slip behavior of water on 2D materials such as graphene and hBN have been both experimentally ,, and theoretically ,,, determined. These studies have shown that water’s wetting and flow properties can significantly depend on the surface’s chemical composition , and morphology, ,,, as these affect the electrostatic and dispersion forces operative between the solid and water .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation